Tantangan dan Peluang Etika Bisnis Islam dalam Strategi Pemasaran Pengusaha Muslim Kota Jambi di Era Digitalisasi - Mutia, Tri; Anggun Lestari, Leni Tania; Amry, Ary Dean; Nabila, Dhea Riqqa; Afrilian, Bima; Lailatifa, Lailatifa (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2024)
The challenges and opportunities of Islamic business ethics in the marketing strategies of Jambi City Muslim entrepreneurs in the digitalization era are an important subject in the context of modern economics. This research outlines the importance of exploring the aspect as it combines two crucial dimensions: Islamic business ethics and marketing strategies in the context of digitalization. Although several studies have discussed Islamic business ethics and digital marketing strategies separately, there has been no research that integrates these two aspects holistically, especially in the specific context of Jambi City. The problem with previous research lies in the lack of emphasis on the intersection between Islamic business ethics and digital marketing strategies, as well as the lack of focus on local contexts such as Jambi City. The formulation of the problem in this research is how the challenges of Islamic business ethics in the digitalization era can be integrated in the digital marketing strategy of Muslim entrepreneurs in Jambi City, as well as what opportunities are available for Muslim entrepreneurs in utilizing brand marketing in accordance with Islamic business ethics. This research uses a qualitative approach with in-depth interviews and content analysis to obtain data. The main finding of this study is that the integration of Islamic business ethics in digital marketing strategies can increase consumer trust, strengthen brands, and increase customer loyalty. Recommendations for future research include the development of practical guidelines for Muslim entrepreneurs in Jambi City in integrating Islamic business ethics in their digital marketing strategies.